Śrīmataṅgamunikr̥ta Br̥haddeśī : mūla-pāṭha Hindī anuvāda - Mataṅga, Muni, 5th cent.; Kshīrasāgara, Dattātreya Bālakr̥shṇa. (Jayapura : Pablikeśana Skīma, 1998)
Ancient treatise, with translation, on music; critical edition.
Hindi and Sanskrit.
Keywords: Music theory -- India -- Early works to 1800.